Experimental estimation of velocities and anisotropy of a series of Swedish crystalline rocks and ores - Malehmir, A.; Andersson, M.; Lebedev, Maxim; Urosevic, Milovan; Mikhaltsevitch, Vassili (Wiley-Blackwell Publishing Ltd., 2013)
To provide a guide for future deep (<1.5 km) seismic mineral exploration and to better understand the nature of reflections imaged by surface reflection seismic data in two mining camps and a carbonatite complex of Sweden, more than 50 rock and ore samples were collected and measured for their seismic velocities. The samples are geographically from the northern and central parts of Sweden, ranging from metallic ore deposits, meta-volcanic and meta-intrusive rocks to deformed and metamorphosed rocks. First, ultrasonic measurements of P- and S-wave velocities at both atmospheric and elevated pressures, using 0.5 MHz P- and S-wave transducers were conducted. The ultrasonic measurements suggest that most of the measured velocities show positive correlation with the density of the samples with an exception of a massive sulphide ore sample that shows significant low P- and S-wave velocities. The low P- and S-wave velocities are attributed to the mineral texture of the sample and partly lower pyrite content in comparison with a similar type sample obtained from Norway, which shows significantly higher P- and S-wave velocities.Later, an iron ore sample from the central part of Sweden was measured using a low-frequency (0.1–50 Hz) apparatus to provide comparison with the ultrasonic velocity measurements. The low-frequency measurements indicate that the iron ore sample has minimal dispersion and attenuation. The iron ore sample shows the highest acoustic impedance among our samples suggesting that these deposits are favourable targets for seismic methods. This is further demonstrated by a real seismic section acquired over an iron ore mine in the central part of Sweden. Finally, a laser-interferometer device was used to analyse elastic anisotropy of five rock samples taken from a major deformation zone in order to provide insights into the nature of reflections observed from the deformation zone. Up to 10% velocity-anisotropy is estimated and demonstrated to be present for the samples taken from the deformation zone using the laser-interferometery measurements. However, the origin of the reflections from the major deformation zone is attributed to a combination of anisotropy and amphibolite lenses within the deformation zone.